(untitled) (Journal of EAHIL, 2017)
The theme of this year’s IFLA Conference, held in Lyon between 16 – 22 August, was Libraries, Citizens, Societies: Confluence for Knowledge. I hadn’t thought about its full significance until I arrived in Lyon, the second largest city in France after Paris, situated, indeed, at the confluence of two of the largest French rivers: the Rhone and the Saone. The place that inspired such a generous theme proved to be not only an excellent venue for the Conference, but it also charmed everyone with its majestic views over the two rivers, its architecture and beautiful parks, its museums and history going back to the ancient times, and, not least, the warm and stylish hospitality of its people.